Different Methods, Different Standards? A Comparison of Two Finnish Reference Budgets - Mäkinen Lauri (SAGE, 2022)
According to Principle 14 of the European Pillar of Social Rights, everyone should have the right to adequate minimum income benefits that ensure a life in dignity. Reference budgets have been proposed to monitor this principle. Reference budgets are priced baskets of goods and services that represent a given living standard. At the moment, no common methodology for constructing reference budgets exists; instead, different methods are used to construct them. This study sought to compare the approaches and results of two Finnish reference budgets: one created by the Centre for Consumer Society Research (CCSR), and the second by the ImPRovE project. The purpose of the article is to respond to a gap in existing literature around how different methods for constructing reference budgets impact their outcomes. The two reference budgets offer a strong basis for comparison because they both sought to capture the same living standard in the same context for similar household types (single woman, single man, heterosexual couple, and heterosexual couple with two children), while using different approaches. The results suggest that the two reference budgets arrive at different estimates of what is needed for social participation. Ultimately, we found that the most significant differences between the budgets were housing and mobility costs for the couple with two children due to differences in information bases, selection criteria, evaluators, and pricing. The study makes a significant contribution to the literature because it is one of the first to explore how different approaches to constructing reference budgets affect their outcomes. The results suggest that clear criteria for constructing reference budgets are needed to monitor Principle 14 of the European Pillar of Social Rights.